PENGARUH RISIKO, MANFAAT, DAN KEMUDAHAN TERHADAP KEPUTUSAN MINAT BELANJA ONLINE - Anita Yuliati; Makmur (Hirarki : Jurnal Ilmiah Manajemen dan Bisnis, 2025)
This study aims to see how the influence of risks, benefits, and convenience on online shopping interest decisions in Sialang Rindang village. The population in this study are online shopping consumers in Sialang Rindang village. The sample used in this study was 95 people. The variables in this study are risk as a variable (X1), benefits as a variable (X2), convenience as a variable (X3), online shopping interest decisions as a variable (Y). Data collection techniques using a questionnaire. Data analysis used the SmartPLS 4.0.9.2 application program. The results obtained in this study are that the risk does not significantly influence the decision of online shopping interest, the benefits do not significantly influence the decision of online shopping interest, convenience has a significant effect on the decision of online shopping interest. The online shop needs to maintain or improve e-commerce services so that consumers still feel the convenience so that consumers will make purchases, especially in online shopping.